Space use by giant anteaters (Myrmecophaga tridactyla) in a protected area within human-modified landscape - Bertassoni, Alessandra (2020)
Spatial ecology data are essential for conservation purposes, especially when extinction risk is influenced by anthropogenic actions. Space use can reveal how individuals use the habitat, how they organize in space, and which components are key resources for the species. We evaluated the space use and multiscale habitat selection of giant anteaters (Myrmecophaga tridactyla), a vulnerable Neotropical mammal, in a Cerrado site within a human-modified landscape in southeastern Brazil. We used GPS transmitters to track eight anteaters in the wild. With the resulting dataset, we estimated home range and core-area sizes and then used two overlap indexes. We assessed habitat selection by compositional analysis and analyzed events of spatio-temporal proximity. The average Brownian bridge kernel estimate of home range size was 3.41 km2 (0.92–7.9). Regarding home range establishment, five individuals showed resident behavior. Males (n = 4) had larger home ranges and were more active than females (n = 4). Despite the spatial overlap of home range (above 40% in four dyads), maximum temporal space sharing was 18%. Giant anteaters were found in proximity. Habitat selection favored savanna, and exotic timber plantation was always avoided. Roads and built-up areas were selected secondarily at the landscape level. The selection of anthropogenic sites denotes behavioral plasticity regarding modified habitats. However, the high selectivity for savanna, at all levels, demonstrates a high dependence on natural habitats, which provide the necessary resources for the species. The recurrent proximity of male–to-female anteaters may indicate reproductive behavior, which is essential for maintaining this isolated population.